Improved trench planting method of sugarcane for water saving, enhancing productivity and income - PRAKASH, SATYA; SINGH, MAHAVIR; KUMAR, ASHOK (Journal of Soil and Water Conservation, 2020)
A study was conducted to assess the improved trench planting method of sugarcane during the 2015-16 and 2016-17 at farmers’ field in Saharanpur district of Uttar Pradesh. In this technique, two eyes piece of sugarcane variety CO-0238 treated with 0.2% carbendazim were sown in trench at a distance of 120 cm line to line during the first week of October. The area between the two rows was covered with lentil (Pant Masoor-8) as intercrop. Study revealed that in this technique, farmers got 1152 qt/ha as average yield in comparison to the conventional planting method (650-750qt/ha). The improved technique resulted in 53.60% higher yield with water saving of 28.57% over conventional method.